Interaction between factors determining the formant structure of long and short vowels in standard Lithuanian: A pilot study - Švageris, Evaldas (Kalbotyra, 2024)
This article aims to determine the relative power and hierarchy of factors that directly impact the distribution of vowels F1 and F2. For this purpose, statistical analysis (ANOVA) has been conducted. Three Lithuanian vowels [ɑː/ɐ], [uː/ʊ], and [iː/ɪ] (the so-called corner vowels), and four factors (the phonological quantity, speakers, focus, and consonants/voiceless plosives) were chosen for the analysis. The results revealed that the hierarchical order of factors primarily depends on vowelsʼ height/frontness. The consonantal factor most influences the formant structure of back vowels, while that of front vowels is more influenced by phonological quantity. Differences in factor hierarchy are reflected in several observed correlations: the openness/closeness of vowels and focus (the more open the vowel, the more its formant structure depends on the prosodic factor), the frontness/backness of vowels and voiceless plosives (the consonantal factor influences back vowels more), and phonological quantity (the formants of short and long front high vowels differed the most). This study is to be extended in the future with a larger dataset.